Body Image Dissatisfaction and Disordered Eating in NCAA Division III Collegiate Student-Athletes - Yoder, Alyssa; McIntyre, Christine; Nelson, Stephanie (My University, 2014)
Distorted body image influencing eating behaviors is a growing issue that is prevalent among society and athletics. It is important for healthcare providers to investigate the psychosocial aspects of eating disorders and body image in order to help various athletic populations. The primary purpose of the study was to raise awareness of body image and altered eating behaviors that may have gone unnoticed in an unexpected sport population.
Color poster with text, images, tables, and charts.
Keywords: Body image; Eating disorders; College athletes; Posters